The Nature and Determinants of High-value Household Deposits in the Euro Area - Kochaniak, Katarzyna (Central and Eastern European Economic Review, 2017)
This paper analyses the occurrence and nature of high-value deposits in selected euro area countries and the determinants of a household’s propensity to possess them. The analysis is conducted on household-level data and based on logistic regression. Due to the rarity of high-value deposits in euro area households, the sample of households surveyed is balanced in accordance with G. S. Maddala’s approach. The results reveal considerable diversification in high-value deposits as a proportion of total deposits in euro area households. Some of the features of households and reference persons, such as attitudes to financial risk, saving aims, overall investment preferences, and the priority accorded to deposits compared to other financial assets, suggest that high-value deposits are of a long-term nature. The study finds that wealth, and certain socio-demographic characteristics, have a statistically significant influence on the likelihood of holding high-value deposits.